Islamic education: lessons of globalization - I.V. Brylina; M.A. Suwandi (Векторы благополучия: экономика и социум)
Relevance. The era of globalization has created new challenges for Islamic education. In the new socio‐cultural conditions, it must use its adaptive potential to cope with the challenges and use new opportunities to remain relevant. Methods. Bibliographic, analytical, comparative. In this case, the use of literature in the form of e‐books, books, articles, journals and other research results includes this discussion. The article identified the following main challenges associated with the problem of Islamic education: the influence of external culture; changes in the paradigm of education; global competition. The following growth points are highlighted and characterized as opportunities for the development of Islamic education: character factors and moral sustainability; integration of technology into the learning process; and International cooperation. Aim. To identify the main challenges of global Islamic education and significant results of responding to them. Results. It is concluded that Islamic education, in order to counter the challenges of globalization, must solve a dual task: always as a social demand for the preparation of a competent, competitive specialist at the global level, possessing and capable of transferring knowledge in new products, services and technologies, as well as a personal demand – at the stages of a collective personality, capable of self‐development based on academic knowledge and high moral qualities, corresponding to Islamic teachings.